3D morphometric evaluation of palatal rugae among Malaysian Malay population - Al-Selwi, Abdullah Abdulkhaleq Mohammed (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2022)
Palatal rugae pattern may have a promising and interesting future for human identification purpose. Previous studies showed that palatal rugae pattern has a lot of morphological and dimensional characteristics that are different from a person to another even among the identical twins. In fact, palatal rugae are anatomically located in a well protected place, behind boons, teeth, cheeks and lips, which provides a good alternative option for human identification in mass disasters and accidents. This study aimed to evaluate the variability and uniqueness of palatal rugae among Malaysian Malays using 3D dental models. A 3D Next Engine Laser scanner (USA) was used to digitize plaster dental casts of 130 Malaysian Malay patients (65 males and 65 females) obtained from the archive of Orthodontic Clinic, Hospital Universiti Sains Malaysia. The resulting 3D models were highlighted using Paint 3D software (USA) for the purpose of rugae shape assessment. Rugae size category and direction were assessed using 3Matic research software (Belgium). The classification method of Thomas and Kotze (1983) as described by Kapali et al. (1997) was adopted. Palatal rugae uniqueness was performed by superimposing 42 pairs of digital models (21 models were duplicated from the same patients and 21